Mental Accounting dan Perilaku Keputusan Investasi: Analisis Perbedaan Berbasis Sosial Kultural - Putriana, Astia; M. Riduan Abdillah; Gati Anjaswari (Shafin: Sharia Finance and Accounting Journal, 2023)
The purpose of this study was to analyze the effect of mental accounting on investment decision behavior and to analyze whether are differences in investment decision behavior in socio-cultural as measured by gender and domicile. The population in this study were college students of accounting program class at Politeknik Negeri Tanah Laut. Politeknik Negeri Banjarmasin and Universitas Islam Negeri Antasari Banjarmasin. The samples in this study are 171 college students, using the purposive sampling technique. Data collected by online and offline questionnaires. The gathered data were analyzed using regression analysis and independent sample t-test. The results of this study indicate that mental accounting has a significant effect on investment decision behavior. Meanwhile, there is no difference between men and women in terms of investment decision behavior. Also, there is no difference between urban and rural respondents in terms of investment decision behavior. This research provides insight to pay attention in case of mental accounting for young investors.